(untitled) (Damascus University Journal for engineering sciences, 2024)
Nowadays, energy efficiency has become the crucial criterion for the consumer when replacing energy consuming devices. The phase change Materials (PCMs) store the thermal energy in its latent form between the liquid and solid states at a small temperature change range. For this reason, it can be used in household refrigerator and freezer for increasing energy efficiency and a level of energy classification of refrigerators. In this paper, the type and thickness of the phase change material that can be included in domestic freezers and its impact on the performance indicators of the refrigeration cycle were determined, coefficient of performance and the second law in thermodynamic, as well as the evaporation temperature and destructive exergy in each part of the refrigeration cycle. Evaporation temperature will be increased by 18.3% when including the phase change material (PCM), which lead to increase in the coefficient of performance by 13.4% and decrease in destroyed exergy by 9.9%, as well as a decrease in power consumption by 8.1%. The operating time will be increased by 33% and the compressor off time increased by 70% as well.